Respons Pertumbuhan dan Produksi Beberapa Varietas Tomat (Lycopersicum esculentum L.) Dataran Rendah Terhadap Pemberian Pupuk Kandang Ayam - Ali Zainal Abidin; Emmy Harso Kardhinata; Yusuf Husni (Universitas Sumatera Utara, 2014)
The purpose of the study was to determine the growth response and yield of some varieties oflowland tomato (Lycopersicum esculentum L.) under application of chicken manure. The researchwas conducted at Pasar I Tanjung Sari, Medan, of 25 meters above sea level, from June until August2013. The research design is a randomized block design with two factors, tomato varieties; Rempai,Vida and Super King, and chicken manure’s dosages; 0, 250, 500 and 750 g/polybag. Parametersobserved were plant height (cm), the number of fruit per plant, the number of bunches, the numberof fruit per bunch, average fruit weight (g) and heritability. The results showed that tomato varietieshave significant different on plant height, average fruit weight, the number of bunches, the numberof fruit per plant and the number of fruit per bunch, dosage of chicken manure showed significantparameters plan height, the numberof bunches and the number of fruit per bunch. Interaction of bothtreatments gave significant different on plant height, the number of bunches, the number of fruit perplant and the number of fruit per bunch.Key words : lowland tomato variety, chicken manure